(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Type 2 diabetes mellitus (T2DM) is a well-known healthcare problem globally. Several factors, including vitamin D level influence cardiovascular diseases. This study was aimed to determine the association of vitamin D (25 [OH] D) levels and serum lipid profiles with T2DM in Bangladesh. The data (n = 111) were collected from the patients’ register record book of BIHS General Hospital (Mirpur, Dhaka). Clinical (age, gender) and biochemical (fasting glucose level, after meal glucose level, HbA1C, lipid profile (HDL, LDL, TG, cholesterol) and 25-hydroxy vitamin D information were included for analysis. Independent sample t-test (two-tailed) was used to compare diabetic (cases, n = 70) and non-diabetic (control, n = 41) groups. Correlation analysis and multiple linear regression assessed unadjusted and adjusted relations between vitamin D levels and other variables, respectively. There was a statistically significant (p <0.001) difference identified in vitamin D levels (mg/dl) between diabetic [mean (range): 23.3 (10.20-38.4)] and non-diabetic [mean (range): 26.9 (20.5-51.4)] subjects. Significantly higher triglyceride, total cholesterol and blood glucose (fasting and after meal) levels were observed in diabetic subjects compared to non-diabetic subjects. However, HDL level was significantly lower in diabetic patients than in non- diabetic patients (40.15 ± 5.56 vs. 42.74 ± 5.72 mg/dl). Pearson correlation analysis exhibited a significantly positive correlation of vitamin D deficiency with glycated hemoglobin (HbA1C) (r = 0.195, p = 0.040), total cholesterol (r = 0.567, p = 0.046), and LDL (r = 0.897, p = 0.003) levels. Multiple regression analysis showed that vitamin D deficiency was significantly associated with higher glycated hemoglobin A1C (β = - 0.097, p = 0.039), fasting blood glucose (β = - 0.119, p = 0.011), total cholesterol (β = - 0.160, p = 001) and triglyceride (β = - 0.201, p < 0.001) levels. Additional extended and thorough randomized controlled clinical trials are required to draw a more definitive conclusion and accumulate more substantial evidence regarding the positive impact of vitamin D supplements on type 2 diabetes mellitus (T2DM). Bangladesh Pharmaceutical Journal 27(2): 175-181, 2024 (July)